Crisis management in construction projects - Loosemore, Martin 1962- (ASCE Press, 2000)
"This book focuses on preventing crises and, if that's not possible, turning them to advantage. It draws lessons from a range of industries, concluding that the secret of effective crisis management is balancing prevention with control. Unfortunately, crises have built-in defense mechanisms that cause people to act in ways that makes this difficult. The book also gives advice as to how to overcome the built-in defense mechanics that cause people to act in way that may impede effective crisis management."